Boosting of fusion reactions initiated by laser accelerated proton beam in a non-thermal neutral and non-neutral proton-boron plasma - Nissim, N.; Henis, Z.; Eliezer, S.; Schweitzer, Y.; Daponta, C.; Moustaizis, S. (Frontiers in Physics, 2024)
In this paper we explore the possibility of boosting the reactivity of non-thermal proton-boron fusion triggered by an external proton beam in a plasma at densities near and lower than solid density and temperature characteristic to laser plasma interaction. Suprathermal protons generated by collisions with alpha particles, as well as energetic protons created by the beam protons that do not undergo fusion during the stopping down in the bulk plasma, are accounted for. In addition, we conduct calculations for non-neutral plasma, motivated by recent suggestion that the number of fusion events in such system may be increased.